Evaluation of the In Vitro Behavior of Electrochemically Deposited Plate-like Crystal Hydroxyapatite Coatings - Cotrut, Cosmin M.; Blidisel, Alexandru; Vranceanu, Diana M.; Vladescu (Dragomir), Alina; Ungureanu, Elena; Pana, Iulian; Dinu, Mihaela; Vitelaru, Catalin; Parau, Anca C.; Pruna, Vasile; Magurean, Mihai S.; Titorencu, Irina (Biomimetics (Basel, Switzerland), 2024)
The purpose of coatings is to protect or enhance the functionality of the substrate material, irrespective of the field in which the material was designed. The use of coatings in medicine is rapidly expanding with the objective of enhancing the osseointegration ability of metallic materials such as titanium. The aim of this study was to obtain biomimetic hydroxyapatite (HAp)-based coatings on titanium by using the pulsed galvanostatic method. The morphology of the HAp-based coatings revealed the presence of very thin and wide plate-like crystals, grown perpendicular to the Ti substrate, while the chemical composition highlighted a Ca/P ratio of 1.66, which is close to that of stoichiometric HAp (1.67). The main phases and chemical bonds identified confirmed the presence of the HAp phase in the developed coatings. A roughness of 228 nm and a contact angle of approx. 17° were obtained for the HAp coatings, highlighting a hydrophilic character. In terms of biomineralization and electrochemical behavior, it was shown that the HAp coatings have significantly enhanced the titanium properties. Finally, the in vitro cell tests carried out with human mesenchymal stem cells showed that the Ti samples coated with HAp have increased cell viability, extracellular matrix, and Ca intracellular deposition when compared with the uncoated Ti, indicating the beneficial effect.